1987
DOI: 10.1227/00006123-198710000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Hyperthermia for Malignant Brain Tumors: Preliminary Results of Clinical Trials

Abstract: Local hyperthermia by 13.56-MHz radiofrequency (RF) capacitive heating was evaluated in 16 patients with malignant brain tumors. Intracranial heating during operation was performed in 4 patients. RF applicators with a cooling system were placed on the cerebral convexity and medial brain surface with the tumor between them. RF power was controlled to maintain the brain temperatures under 40 degrees C. Under this condition, the highest temperature of each tumor varied from 44 to 49 degrees C. After heating for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Tanaka et al [5] showed that RF capacitive heating can be applied safely to treat a malignant tumor in the human cerebrum. In neurosurgery, repeated RF heating was found to be practical and useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tanaka et al [5] showed that RF capacitive heating can be applied safely to treat a malignant tumor in the human cerebrum. In neurosurgery, repeated RF heating was found to be practical and useful.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of RF catheter ablation is its ability energy to a discrete area without stimulating muscles or nerves [2]. Recently, RFA for a larger part of the visceral organs or intra-abdominal tumors has been reported [3][4][5][6][7][8]. The development of bipolar and multiple-electrode RFA probes Nakagawa et al has enabled the creation of much larger lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the past 10 years, we have been developing hyperthermic therapy for malignant brain tumors 30 and have recently completed a new technique using an RF antenna which can be inserted into optional regions of the brain with a stereotactic apparatus. 28 This antenna can apply sufficient regional hyperthermia without causing adverse reactions, even if the brain tumor exists in an eloquent area.…”
Section: Thermosensitive Liposome and Hyperthermia Treatmentmentioning
confidence: 99%
“…There has been much interest in studying the effects of heat on the brain (Sminia et al, 1994;Haveman et al, 2005). A number of well-localized, mainly interstitial, invasive hyperthermia combination therapies have been applied for gliomas (Tanaka et al, 1987;Sneed et al, 1991Sneed et al, , 1992Sneed et al, , 1998Stea et al, 1990Stea et al, , 1994Moran et al, 1995;Fiorentini et al, 2006;Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%